Implementation of Predict-Observe-Explain (POE) Strategy to Reduce Misconception in Thermochemistry - Zakiyah, Imroatuz; Widodo, Wahono; Tukiran, Tukiran (International Journal for Educational and Vocational Studies, 2019)
This research aims to determine that the implementation of the POE (predict-observe-explain) strategy can be used to correct misconceptions in thermochemistry. This research uses One Group Pretest-Posttest Design. This research was conducted in class XI MIA 5 students at Bhayangkari 3 Porong Senior High School. The sample used was 33 students who were divided into 6 heterogeneous groups. The students are given a conceptual understanding test as pretest and posttest in the form of a three-tier diagnostic test which amounts 20 questions. After pretest the next stage is to do remediation given learning process using worksheet of POE strategy. Then the results of pretest and posttest were then analyzed using Wilcoxon signed rank test. The result is POE (predict-observe-explain) strategy can be used to correct misconceptions in thermochemistry sub-topic for students in class XI of Bhayangkari 3 Porong Senior High School. This is indicated by a decrease in the percentage of students' misconceptions from 66.36% to 6.36%. In addition, based on the Wilcoxon Sign Rank Test, Asymp. Sig (2-Tailed) has 0 value, it means hypothesis 0 is rejected, which means there is a significant influence on the implementation of learning with POE strategies to improve the student’s status of knowing the concept.